Association between cardiologist evaluation and mortality in myocardial injury after non-cardiac surgery. Issue 9 (16th August 2021) - Park, Jungchan; Oh, Ah Ran; Kwon, Ji-hye; Kim, Sojin; Kim, Jeayoun; Yang, Kwangmo; Choi, Jin-Ho; Kim, Kyunga; Ahn, Joonghyun; Sung, Jidong; Lee, Seung-Hwa
Abstract : Objective: Myocardial injury after non-cardiac surgery (MINS) is strongly associated with mortality, but few studies assessed treatment strategies. This study aimed to identify whether evaluation by cardiologists could reduce mortality in MINS patients. Methods: From a single-centre retrospective cohort, we enrolled a total of 5633 adult patients diagnosed with MINS between January 2010 and June 2019. The patients were divided into two groups based on evaluation by cardiologist, which was defined as a cardiology consultation or transfer to the cardiology department. For the outcome, 30-day mortality was compared in crude and propensity-score matched populations. Results: Of a total of 5633 patients, 2120 (37.6%) were evaluated by cardiologists and 3513 (62.4%) were not. Mortality during the first 30 days after surgery was significantly lower in MINS patients who were evaluated by cardiologists compared with those who were not (5.8% vs 8.3%; HR, 0.64; 95% CI 0.51 to 0.80; p<0.001 for all-cause mortality and 1.6% vs 2.0; HR 0.62; 95% CI 0.40 to 0.96; p=0.03 for cardiovascular mortality). The propensity score matched analysis showed similar results (5.6% vs 8.6%; HR 0.64; 95% CI 0.50 to 0.81; p<0.001 for all-cause mortality and 1.3% vs 2.2%; HR 0.58; 95% CI 0.35 to 0.95; p=0.03 for cardiovascular mortality). Conclusions: Cardiologist evaluation was associated with lower mortality in patients diagnosed with MINS. Further studies are needed to identify effective treatment strategies for MINS. Trial registration number: KCT0004244.